UPAYA PENINGKATAN MOTIVASI BELAJAR SENI TARI PADA SISWA SMP MELALUI KEGIATAN APRESIASI SENI - -, Herlinah (Imaji: Jurnal Seni dan Pendidikan Seni, 2015)
This research was aimed at improving learning motivation to dance and finding a learning model which is appropriate to State Junior High School Students in Yogyakarta. The steps of the research were adopted from a design model developed by Kemmis & Mc.Taggart. It consists of four components, namely plan, action, observation and reflection, which form a chain in a cycle. The instruments of the research include class observation sheets, field notes and questionnaires. The motivation improvement was measured through the learning process and result. The aspects measured in the learning process are attention, relevance, self-confidence and satisfaction. The learning result was evaluated through live art appreciation activities, which were also recorded in video. It was known that the routine activities could increase the students’ learning motivation to dance. Key words: learning motivation, art appreciation